PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA PENGGELAPAN DALAM JABATAN DI PERSEROAN TERBATAS - Zainudin Hasan (Universitas Bandar Lampung (UBL), 2020)
The problem in this study is how is the responsibility of the perpetrators of embezzlement in a position in Anugerah Bina Usaha Nusantara Limited Company? The research method used in the research is the normative and empirical approaches. Based on the results of research and studies obtained, it can be concluded that the judge's judgment in deciding the perpetrators of embezzlement in positions of limited liability company, that the description of the guilty elements of the defendants has been considered one by one by the panel of judges. The responsibility of the perpetrators of embezzlement in positions of limited liability in the intellectually limited company has objectively demonstrated the ability and ability to be physically and physically fit so that there is no obstacle to accountability for his actions legally. Suggestions that can be delivered are that the judge in this case should be able to decipher the facts and dig deeper about who the intellectual actor behind the crime of embezzlement in the Limited Liability Company.